Penggunaan Media Sosial Instagram Dalam Meningkatkan Literasi Kesehatan Pada Mahasiswa - Nur Anisah; Maini Sartika; Hendra Kurniawan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
This study entitled "Use of Instagram Social Media in Improving Health Literacy in Syiah Kuala University Students" aims to assess the use of Instagram social media by seeking information about health in improving student health literacy at Syiah Kuala University. This study uses the uses and gratifications theory. This research is a qualitative research with descriptive type. The criteria for informants in this study were Syiah Kuala University students, active users of Instagram social media, and using Instagram for health-related purposes. Data collection methods used are interviews, and documentation. The results of this study indicate that Instagram is proven to be able to meet the needs of students to get access to the health information needed. The seven informants have good conceptual knowledge so that they can improve their health literacy through the use of Instagram social media. Students also have a better understanding of health after being exposed to health content on Instagram. This is in line with the students' motives to obtain useful health information in increasing their understanding of health, so that they can make the right health decisions, it contributes to improving students' health literacy.